2022
DOI: 10.3390/ijerph19159042
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Elements and Relationships among Elements in Intervertebral Disc Degeneration

Abstract: Intervertebral disc degeneration (IVDD) is a complex and progressive process of disc aging. One of the most important causes of changes in the internal environment, leading to IVDD, can be changes in the concentration of individual metal elements. This study aimed to analyze the concentrations of copper, iron, manganese, lead, zinc, sodium, potassium, phosphorus, and calcium in the degenerated intervertebral discs of the lumbosacral spine, compared to healthy intervertebral discs. The study group (S) consisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Knockdown of FDX1 alleviated cell death, suggesting the presence of cuproptosis in IDD. Trace element analysis revealed that a higher concentration of copper was found in healthy disks than in IDD disks 41 . The upregulation of cuproptosis proteins coupled with the simultaneous reduction in detectable dry weight of copper in IDD suggests that the regulation of copper homeostasis may play a critical role in this phenomenon.…”
Section: Discussionmentioning
confidence: 93%
“…Knockdown of FDX1 alleviated cell death, suggesting the presence of cuproptosis in IDD. Trace element analysis revealed that a higher concentration of copper was found in healthy disks than in IDD disks 41 . The upregulation of cuproptosis proteins coupled with the simultaneous reduction in detectable dry weight of copper in IDD suggests that the regulation of copper homeostasis may play a critical role in this phenomenon.…”
Section: Discussionmentioning
confidence: 93%
“…Cuproptosis is a copper-triggered manner of mitochondrial cell death [ 38 ]. Mounting evidence has revealed that copper metabolism plays an important role in multiple biological processes of IDD [ 14 , 39 ]. It has been verified that copper complexes exert a toxic and immunogenic effect on intervertebral discs [ 15 ], suggesting that cuproptosis may exist in the pathological process of IDD.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in copper metabolism can trigger multiple disorders such as obesity [ 9 ], glioblastoma [ 10 ], acute myeloid leukaemia [ 11 ], type 2 diabetes [ 12 ], and various malignancies [ 13 ]. With the further study on copper, researchers have found that the concentration of copper element shows significant differences between the tissues of IDD and normal controls [ 14 ], and copper could result in severe disc degeneration [ 15 ]. Therefore, we hypothesize that cuproptosis may influence the pathogenesis of IDD by modifying the transcript level of genes related to cuproptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The connection between genes involved in zinc metabolism and IVDD has not been extensively studied. Staszkiewicz R et al [ 64 ] investigated the relationship between the concentration of local metal ions in the patient’s disc tissue and the degree of progression of IVDD. They discovered that the strongest relationships were noted between the concentrations of zinc.…”
Section: Discussionmentioning
confidence: 99%